Factors Associated with Multi-Biologic Use in Psoriasis Patients at an Academic Medical Center and Review of Biologic Survival. Issue 1 (January 2023) - Hadeler, Edward; Kumar, Sugandh; Yeroushalmi, Samuel; Hong, Julie; Wallace, Elizabeth; Han, George; Mosca, Megan; Bartholomew, Erin; Chung, Mimi; Hakimi, Marwa; Reddy, Soumya; Scher, Jose; et al.
Background: Despite their impressive efficacy in phase 3 trials, biologic agents for psoriasis (PsO) may lose efficacy over time. The factors associated with loss of efficacy have yet to be fully elucidated. Objective: We aimed to identify factors associated with PsO patients using multiple biologics in comparison to patients who used 1 biologic. We also reviewed the literature comparing the survival of different biologic agents for PsO. Methods: We examined clinical data from 222 psoriasis patients at the University of California San Francisco, of whom 51 reported use of 3 or more biologics and of whom 171 reported use of only a single biologic agent at the time of enrollment into a research database from 2006-2020.This study was IRB-approved at UCSF (#10-02830) and all subjects provided written informed consent. We performed univariate and multivariate regression analysis to identify significant demographic features, clinical features, and co-morbidities associated with multi-biologic use. We performed a literature review of studies comparing psoriasis biologic survival at 1, 2, and 5 years and factors associated with single biologic failure. Results: In univariate analysis, duration of PsO, initial presentation of PsO on the gluteal cleft, erythrodermic psoriasis, and acne were associated with using 3 or more biologics. In multivariate analysis, duration of PsO, erythrodermic psoriasis, and acne remained significant. Our review of biologic survival revealed differences according to biologic class. Conclusion: We identified novel factors associated with multi-biologic use in PsO. Further studies in this area are needed to achieve a precision medicine approach.